2015
DOI: 10.3109/14767058.2015.1069811
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic markers for newborn congenital heart defect (CHD)

Abstract: Profound differences in cytosine methylation were observed in hundreds of genes in newborns with different types of CHD. There appears to be the potential for development of accurate genetic biomarkers for CHD detection in newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
1
15
0
1
Order By: Relevance
“…Зарегистрированы множественные случаи иНКЛЖ при серповидноклеточной анемии [14,16], беременности [17], нейромышечной патологии [12] и ХПН [13]. Эти наблюдения расширяют спектр этиопатогенетических гипотез от патологии эмбриогенеза к адаптивным патогенетическим механизмам, включающим компенсаторные изменения сердца в неблагоприятных условиях гемодинамической перегрузки и другие эпигенетические факторы [42]. 7.…”
Section: вариабельность нкмunclassified
“…Зарегистрированы множественные случаи иНКЛЖ при серповидноклеточной анемии [14,16], беременности [17], нейромышечной патологии [12] и ХПН [13]. Эти наблюдения расширяют спектр этиопатогенетических гипотез от патологии эмбриогенеза к адаптивным патогенетическим механизмам, включающим компенсаторные изменения сердца в неблагоприятных условиях гемодинамической перегрузки и другие эпигенетические факторы [42]. 7.…”
Section: вариабельность нкмunclassified
“…Multiple prior studies have reported genome-wide DNA methylation profiles from archived dried blood spots using Infinium HumanMethylation450 BeadChips. [ 20 ] [ 21 ]. The Infinium HumanMethylation450 BeadChips array for methylation (Illumina, Inc., California, USA) contains >485,000 CpGs per sample in enhancer regions, coding regions, promoters and CpG islands at a single-nucleotide resolution and requires only 500 ng of genomic DNA per assay.…”
Section: Methodsmentioning
confidence: 99%
“…Epigenetic changes are largely tissue specific and the inaccessibility of the heart in living subjects is a monumental challenge to studying cardiac development in general. Work by our group [ 20 , 21 ] and others [ 22 ] have reported evidence that a significant minority of epigenetic marks in blood DNA mirror similar changes in inaccessible organs such as the heart and the brain respectively. This opens the possibility of ongoing epigenetic analysis of such organs.…”
Section: Introductionmentioning
confidence: 99%
“…Given the clinical significance of CHD and the frequency of missed or late diagnosis, this is a major deficiency. In our prior pilot data [17, 18] cytosine methylation status of blood leucocytes was found to be a potentially useful molecular biomarker for the detection of multiple different categories of CHD. This is consistent with the previously referenced attempts to use epigenetic signatures in leucocytes to detect psychiatric disorders [16].…”
Section: Introductionmentioning
confidence: 99%
“…We therefore reasoned that although not identical, there was likely to be a significant minority of cytosine loci in which parallel epigenetic modifications could be demonstrated in cardiac development genes in general and genes related to ventricular development in the placenta from VSD pregnancies. We had previously demonstrated this phenomenon in multiple categories of CHD using blood (leucocyte) from affected newborns as the surrogate tissue for detecting CHD [17, 18]. Our objective therefore in this proof of concept study was to evaluate the utility of cytosine methylation in placental DNA to elucidate the pathogenesis of and for the detection of isolated non-syndromic VSD.…”
Section: Introductionmentioning
confidence: 99%